ANALISIS USAHATANI JAGUNG HIBRIDA (Zea Mays L) DI NAGARI KINALI KECAMATAN KINALI KABUPATEN PASAMAN BARAT - Anggi Rahmad; Mahmud; Amnilis (Fakultas Pertanian, Universitas Ekasakti, 2021)
The objectives of this study are as follows: To determine the characteristics of hybrid maize farmers in Nagari Kinali, Kinali District, West Pasaman Regency and to analyze hybrid maize farming in Nagari Kinali, Kinali District, West Pasaman Regency. This research was conducted in March 2020. The method used in this research is descriptive method. Determining the location of the study was done deliberately (purposive) with a total sample of 71 people from 247 populations. The data analysis used in this research is qualitative and quantitative. The majority of farmers are in the productive age with the age of 47 - 52 years with 27 people or 38.03%, 22 people or 31.00% of the farmers' education is more dominant, the most dominant farmer's land area is 0.25 -0.50 As many as 58 people or 81.69%, the farming experience has been long enough, namely at most 5 - 6 years as many as 34 people or 47.88% and the production obtained by hybrid corn farmers is Rp. 6,858 Kg/Ha/MT. Revenue amounting to IDR 23,692,154 Ha/MT. Income of IDR 16,153,033 Ha/MT. The total cost is IDR 11,602,388 Ha/MT. Profit of IDR 12,089,766 Ha/MT. Based on the results of the analysis, it shows that the R/C value obtained is 2.04. This figure shows that if the investment is IDR 1, it will get 2.04 revenue. In other words, the farming in the research area is feasible to be cultivated. and BEP which includes: BEP revenue of Rp. 5,965,342 Ha/MT. The production BEP is 7,180.33 Kg/Ha/MT and the BEP is Rp. 1,693.970 /Kg/Ha/MT that the hybrid maize farming in the research location is feasible to be cultivated.